Serum beta2-microglobulin and peripheral blood eosinophils for the assessment of severity and prognosis with omicron variant COVID-19 infection - Tan, Jie; Fang, Hanxi; Hu, Xiao; Yue, Ming; Yang, Junling (Frontiers in Molecular Biosciences, 2024)
BackgroundThe Omicron variant’s high transmissibility has made it the most widespread novel coronavirus variant. Elevated serum β2-MG levels from viral infections and EOS’ role in viral clearance have garnered attention. However, their predictive value for Omicron’s severity and prognosis needs further exploration.MethodsThis retrospective study included 424 patients with confirmed COVID-19 Omicron variant admitted to the Second Hospital of Jilin University in Changchun, China, of whom 128 experienced in-hospital mortality. Patients were divided into high and low groups according to β2-MG and EOS levels; the relationship between disease severity and patient prognosis was analyzed.ResultsOur findings showed that severe-to-critical Omicron patients had higher β2-MG levels than mild-normal patients. Conversely, EOS levels were higher in mild-moderate cases. Both β2-MG and EOS levels normalized when Omicron patients tested negative for nucleic acid. Deceased Omicron patients had significantly lower pre-mortem EOS levels. Elevated β2-MG and lower EOS levels correlated with reduced overall survival. Multivariate COX regression analysis indicated that elevated β2-MG was an independent adverse prognostic factor for Omicron patients.ConclusionHigh serum β2-MG levels and low eosinophil levels upon admission correlate with omicron variant severity and prognosis. β2-MG is an independent risk factor for poor outcomes in omicron patients.